Quality, textural profiles, oxidative stability and bacterial content during retail display of beef patties formulated with pectin powder - Salam, Sanita; Kwanonin, Kawinna; Nakawiroj, Piyarat; Pastsart, Umaporn (Food Agricultural Sciences and Technology, 2024)
Pectin plays an important role in the food industry as a gelling and stabilizing agent with various bioactive compounds. This study aimed to elucidate the effects of pectin powder (PP) on the quality, texture, oxidative stability and bacterial content of beef patties during retail display. The beef Longissimus thoracis (LT) was ground and divided into 3 groups: 1) control group (0% PP), 2) ground beef supplemented with 1% PP and 3) ground beef supplemented with 2% PP. Then beef patties were made, wrapped and displayed at 4°C for 0, 3, and 6 days. Regarding the product quality, it was found that PP reduced pH and cooking loss, but on the other hand, it increased L*, a* and b* color coordinates of the beef patties (P<0.05). Regarding textural profiles, on day 6 of display, it was found that beef supplemented with 2% PP had the lowest hardness, cohesiveness, gumminess and chewiness, but the highest adhesiveness (P<0.05). However, 1% and 2% PP groups had less springiness compared to the control group (P<0.05). As for oxidative stability, groups with PP had increased antioxidant activity (P<0.05), but still, there was no significant difference in lipid oxidation among all the groups after 6 days of display (P>0.05). In addition, PP had no effect on total bacterial count during retail display (P>0.05). Therefore, from the experimental results it can be concluded that supplementing beef patties with pectin powder can improve their quality and texture by increasing color coordinates, water holding capacity, tenderness, and antioxidant activity.